Transformasi Pembelajaran Pancasila Berbasis Literasi Visual melalui Media Canva pada Siswa Sekolah Dasar - Nurkholifah, Anisa; Nisa, Khoirun; Juwita , Ratan (Insight: Indonesian Journal of Social, Humanity, and Education, 2025)
This study examines the use of Canva to improve elementary school students' visual skills and understanding of Pancasila values in Civics (PPKn) learning. Several obstacles, such as limited internet access and teachers' lack of skills, encourage innovation through interactive visual learning using Canva. This media provides features such as posters, videos, and animations that make learning materials more engaging and easier for students to understand. This study used a literature review method by analyzing 17 articles from Google Scholar using the keyword "learning Pancasila values by developing visual literacy media with Canva." The results showed that Canva successfully improved elementary school students' conceptual understanding, learning motivation, creativity, and visual literacy skills. Canva's advantages include easy access, attractive design, and support for projectbased learning. However, it also has disadvantages, such as dependence on the internet, the presence of paid features, and the need for sufficient digital skills. Therefore, this study emphasizes Canva's effectiveness in Civics (PPKn) learning. Keywords: Canva; visual literacy; PPKn; Pancasila values; elementary school students   ABSTRAK Penelitian ini membahas penggunaan media canva dalam meningkatkan kemampuan visual dan pemahaman nilai-nilai pancasila pada siswa SD dalam pembelajaran PPKn. Beberapa hambatan seperti akses internet yang terbatas dan kurangnya kemampuan guru mendorong inovasi dengan pembelajaran visual interaktif menggunakan canva. Media ini menyediakan fitur seperti poster, video, dan animasi yang membuat materi pembelajaran lebih menarik dan mudah dipahami oleh siswa. Penelitian ini menggunakan metode studi pustaka dengan menganalisis 17 artikel dari Google Scholar yang menggunakan kata kunci "pembelajaran nilai-nilai Pancasila dengan mengembangkan media literasi visual canva". Hasilnya menunjukkan bahwa canva berhasil meningkatkan pemahaman konsep, motivasi belajar, kreativitas, serta kemampuan literasi visual siswa SD. Kelebihan canva mencakup akses yang mudah, desain menarik, serta pendukung pembelajaran berbasis proyek. Namun, ada juga kekurangan seperti ketergantungan pada internet, adanya fitur berbayar, serta dibutuhkannya kemampuan digital yang cukup. Dengan begitu penelitian ini menekankan bahwa canva efektif digunakan dalam pembelajaran PPKn. Kata kunci: Canva, literasi visual, PPKn, nilai Pancasila, siswa SD